Infection of Human Dendritic Cells by a Sindbis Virus Replicon Vector Is Determined by a Single Amino Acid Substitution in the E2 Glycoprotein - Gardner, Jason P. (American Society for Microbiology, 2000)
The ability to target antigen-presenting cells with vectors encoding desired antigens holds the promise of potent prophylactic and therapeutic vaccines for infectious diseases and cancer. Toward this goal, we derived variants of the prototype alphavirus, Sindbis virus (SIN), with differential abilities to infect human dendritic cells. Cloning and sequencing of the SIN variant genomes revealed that the genetic determinant for human dendritic cell (DC) tropism mapped to a single amino acid substitution at residue 160 of the envelope glycoprotein E2. Packaging of SIN replicon vectors with the E2 glycoprotein from a DC-tropic variant conferred a similar ability to efficiently infect immature human DC, whereupon those DC were observed to undergo rapid activation and maturation. The SIN replicon particles infected skin-resident mouse DC in vivo, which subsequently migrated to the draining lymph nodes and upregulated cell surface expression of major histocompatibility complex and costimulatory molecules. Furthermore, SIN replicon particles encoding human immunodeficiency virus type 1 p55(Gag) elicited robust Gag-specific T-cell responses in vitro and in vivo, demonstrating that infected DC maintained their ability to process and present replicon-encoded antigen. Interestingly, human and mouse DC were differentially infected by selected SIN variants, suggesting differences in receptor expression between human and murine DC. Taken together, these data illustrate the tremendous potential of using a directed approach in generating alphavirus vaccine vectors that target and activate antigen-presenting cells, resulting in robust antigen-specific immune responses.